Penerapan Metode Regresi dalam Memprediksi Laba Bersih Penjualan - Sari, Nur Avia Adenta; Nurmalitasari, Nurmalitasari; Nurchim, Nurchim (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Unexpected changes in net profit can make it difficult for XYZ to control costs and make strategic decisions. This study proposes the use of linear regression as a forecasting method for net sales profit as a way to reduce uncertainty in financial planning and assist in business decision-making. This approach was chosen because of its ability to measure and explain the correlation between dependent factors, such as net profit, and independent variables, such as sales volume and operating costs. The analysis procedure includes data exploration, regression modeling, model performance evaluation, and visualization of prediction results, which can be conducted systematically. Considering the findings of this study's evaluation, the model demonstrated excellent performance in predicting net sales profit, with an evaluation result of Root Mean Squared Error (RMSE) of 27778.50, Mean Absolute Error (MAE) of 20084.71, Mean Absolute Percentage Error (MAPE) of 9.88 %. The main advantage of this forecasting is its ability to help businesses improve the accuracy of financial planning, manage operational costs, and develop focused business plans. Additionally, management can avoid overstocking or understocking, set reasonable sales targets, and adjust production levels to market demand through the use of accurate forecasts.